Implementasi Metode Rapid Application Development (RAD) Dalam Pembangunan Sistem Pengajuan KreditBerbasis Progressive Web App - Fredian Septa Nugroho; Umi Rosyidah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The manual credit application process often takes a long time and is prone to various problems, such as recording errors, data redundancy, and the risk of losing important documents. These conditions not only hamper service effectiveness but can also reduce customer satisfaction and the performance of the officers involved. Therefore, this study aims to design and develop a Progressive Web App (PWA)-based credit application system using the Rapid Application Development (RAD) method. This system is expected to be a more efficient, faster, and more accurate solution than the current manual mechanism. PWA was selected based on its ability to provide universal access through a browser without the need for additional application installation, making it more practical for both customers and officers. Meanwhile, the RAD approach allows for an iterative and flexible system development process, with direct user involvement from the design stage through implementation. This aims to ensure the system is truly aligned with real-world needs. The development results indicate that the designed PWA system is capable of supporting the tasks of Account Officers (AO) and Division Heads in managing credit application data. The process includes the pipeline stage, submission, field survey, and credit realization, which is well-documented and accessible in real time. Functional testing using the Black Box Testing method proved that all features functioned according to established specifications. Furthermore, usability testing using the System Usability Scale (SUS) method yielded satisfactory scores, indicating the system's high usability and positive user experience. Therefore, this PWA-based credit application system not only improves process effectiveness and efficiency but also supports transparency, data accuracy, and user satisfaction.